FRI0324 Work Productivity in Primary Sjögren's Syndrome: A Cross-Sectional Multicenter Study. (15th July 2016) - Baldini, C.; Bartoloni, E.; Priori, R.; Carubbi, F.; Alunno, A.; Quartuccio, L.; ,
Abstract : Background: Sjögren's syndrome (pSS) is generally considered a benign disease; however, given the high frequency of fatigue, articular and musculoskeletal pain and/or peripheral neurological disorders among pSS patients, the disease represents a potentially disabling disorder negatively affecting patient quality of life and work productivity. However, only limited information is available regarding the work ability of pSS patients. Objectives: To assess work participation in a multicenter cohort of patients with pSS, and to explore whether work productivity differed across groups of patients when stratified according to disease activity and damage. Methods: Consecutive pSS patients (AECG 2002) were recruited in 5 referral centers. Data collection included clinical examination, patient reported outcome measures (i.e. EULAR SS Patient Reported Index (ESSPRI), oral health impact profile questionnaire (OHIP), ocular surface disease index questionnaire (OSDI), Work Productivity and Activity Impairment Questionnaire (WPAI)) and laboratory assessment. The EULAR SS Disease Activity Index (ESSDAI) and the Sjögren's syndrome disease damage index (SSDDI) were used to assess disease activity and damage. We used data from WPAI and additional information on work participation to assess absenteeism (work time missed), presenteeism (impairment while at work) and overall work productivity loss (absenteeism plus presenteeism) due to pSS. We then compared work participation across patient groups stratified according to disease manifestations by Mann-Whitney U-test or chi-square test as appropriate. Results: A total of 223 patients were included with median (IQR) age 62.5 (53, 69.5) years, median follow-up 5 (3, 11) years, 98% female gender and 56.2% anti-Ro/SSA positivity. Seventy-two patients (32.2%) reported current employment. Patients not reporting employment were retired (29.5%), or unemployed for other reasons (42.9%). On average, employed pSS patients reported a 9% (20%) mean (SD) absenteeism rate, a 35% (23%) mean (SD) presenteeism rate and a 38% (26%) mean (SD) overall work impairment rate due to health. In the entire cohort the mean (SD) activity impairment (AI) was 47, 5% (27%). Primary SS patients with more aggressive disease manifestations, requiring steroids and immunosuppressive drugs, presented the highest rates of absenteeism and disability as assessed by AI. Additional determinants of AI were presence of arthritis (p=0.02) and fibromyalgia (p=0.005). Similarly, patients presenting arthritis reported significantly higher rates of absenteeism (p=0.04). Moreover, higher rates of presenteeism (p=0.02) and work productivity loss (p=0.01) were detected in patients showing a SSDDI≥1. Finally, positive correlations were found between the ESSPRI, the VAS score for pain and fatigue, and the absenteeism rates, presenteeism rates, work productivity loss and AI, respectively (p<0.01). Conclusions: Employment rates were particularly low among pSS patients. Determinants of work disability were fatigue, articular involvement and comorbidities, including fibromyalgia. Disclosure of Interest: None declared